The Role of Facebook and Instagram Hate Speech in Societal Polarization: Evidence from Pakistan in a Global Context - Shahnila; Dr. Muhammad Fahim Baloch; Samar, Dr. Nasreen (Journal of Quranic and Social Studies, 2025)
The research explores the relationship between hate speech on social media and polarization in Pakistan. It examines the relationship between the way hate speech varies in developing, underdeveloped, and developed countries, along with its contribution to the social, political, and cultural divisions. The research examines the role of social media platforms in either fuelling or controlling hate speech and reviews the effectiveness of institutional and government responses in different regions. Finally, the paper recommends that developing, underdeveloped, and developed countries improve policy regulations and digital governance to reduce the negative influence of hate and minimize polarization in society.